FILSAFAT POLITIK KANT DAN RELEVANSINYA BAGI PERLINDUNGAN MARTABAT MANUSIA - Lega, Fransiskus Sales (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Abstract: Political Philosophy of Kant and its Relevance For the Protection of Human Dignity. This article is aimed to explore the concept of political philosopy addressed by Kant. Immanuel Kant is a political philosopher who is very much concerned with  human dignity in  his political philosophy. Politics is an inherent part of human life. No man is apolitic. By politics human being is able to humanize himself and others. Kant emphasized that human is a being with dignity. If politics is undestood as an instrument for humanizing human being, so politics never dehumanize human dignity. On the other hand, it plays a significant role in protecting human dignity. According to Kant, protection to human dignity can be guaranteed by state and  republican constitution and the progress of  international partnership toward everlasting peace, which is free from exploiting war as an instrument of achieving it.Key words: political philosophy, human dignity, state, dan perpetual peaceAbstrak: Filsafat Politik Kant dan Relevansinya Bagi Perlindungan Martabat Manusia. Politik merupakan bagian yang inheren dari kehidupan segenap umat manusia. Tidak ada manusia yang apolitis. Melalui politik manusia mampu memanusiakan diri dan sesamanya.  Kant menegaskan bahwa manusia adalah mahkluk yang bermartabat. Jika politik dilihat sebagai sarana untuk memanusiakan manusia, maka politik tidak pernah boleh melecehkan martabat manusia. Politik harus memainkan peranan penting dalam melindungi martabat manusia. Immanuel Kant adalah filsuf politik yang menempatkan martabat manusia pada pusat filsafat politiknya. Menurut Kant, perlindungan terhadap martabat manusia dapat dijamin oleh negara-negara dan konstitusi yang berbentuk republikan dan  kemajuan  kerjasama internasional demi terciptanya perdamaian abadi tanpa menggunakan perang sebagai sarana mencapainya.Kata kunci: filsafat politik, martabat manusia, negara, dan perdamaian abadi